Plaque removal efficacy of the interdental toothbrush - Kawasaki, Koji; Kambara, Masaki; Doi, Takashi; Uene, Masako; Jin, Koichiro (Journal of Osaka Dental University, 2015)
Daily oral care is an established part of a healthy lifestyle in Japan. Self-care by tooth brushing is the primary way of cleaning the oral cavity. However, a large amount of dental plaque remains in the proximal areas of the teeth even after brushing. As a result, the use of dental floss or an interdental brush for cleaning areas between the teeth is commonly used to complement oral cleaning. We compared the red plaque removal efficacy of plaque disclosed with red disclosing solution by an interdental brush with that by a manual toothbrush. Oral examination and quantitative light-induced fluorescence (QLF) were performed and two parameters were analyzed from the digital images : the mean ΔR (%) and the area (mm2) of the plaque. We examined 10 subjects between 20 and 50 years of age who were students and staff members at Osaka Dental University Hospital. The digital image analysis revealed that plaque could be detected in about 33 regions (41.3%) of the 80 proximal areas measured on QLF digital images of the subjects. When using the interdental brush, the mean ΔR in the experimental group was 33% after tooth brushing had been suspended for 3 days, 26% after 7 days (representing a decrease in the mean ΔR of 20%), and 24% after 14 days (a decrease in mean ΔR of 26%). Although the downward trend in mean ΔR was not observed in the controls, it decreased significantly in the experimental group. The mean area of red plaque after using the interdental brush in the experimental group was 0.18 mm2 after 7 days (a decrease in the area of plaque of 71%), and 0.12 mm2 after 14 days (a decrease in area of 80%). We found that the mean area of plaque decreased significantly in the experimental group. These results suggest that when using an interdental toothbrush we could get about 60% more plaque removal efficacy than when only a conventional toothbrush was used.